Indonesian Migrant Worker Policies and the Vulnerability of Women Migrant Workers to Becoming Trafficking Victims: an Overview of Recent Legislation - Ninik Rahayu (Journal of Southeast Asian Human Rights, 2017)
This study will provide an overview of how migrant worker protection policies should govern all forms of protection for migrant workers, especially women workers who often face violent abuse as overseas domestic workers in receiving countries, and then problems when they return to their villages. It outlines several laws that deal with problems of abuse associated with migration such as the Law Eradication of Trafficking in Person, and other regulation. Indonesia Government has made a good initiative by amending the policies of migrant workers with the aim of prioritizing protection, including how to harmonize other policies. This is a good starting point for implementing all commitments to the extent that commitments to protect migrant workers, especially women migrant workers who are still vulnerable to violence and threats of trafficking.